POLA KOMUNIKASI ANTARPRIBADI DOSEN DENGAN MAHASISWA SELAMA PERKULIAHAN JARAK JAUH DI MASA PANDEMI COVID-19 (Studi Fenomenologi Pada Mahasiswa dan Dosen UPN "Veteran" Jakarta) - Febri Irawan (2022)
The COVID-19 pandemic that occurred in Indonesia, made the government issue a Government Regulation to adjust activities that occurred in the midst of a pandemic. One of those affected is the education sector. Lectures which are usually conducted face-to-face must be carried out boldly to minimize the spread of the virus. The purpose of this phenomenological study is to understand in depth the pattern of interpersonal communication during distant lectures during the COVID-19 pandemic for lecturers and Communication Studies students at FISIP UPNVJ. This study uses qualitative research methods with a phenomenological approach to describe individual experiences with distance learning during the COVID-19 pandemic. The information was obtained by eight people who were selected according to the research criteria. Data collection techniques used in this study were in-depth interviews and literature study. The result of this research is that long-distance interpersonal communication between lecturers and students is felt by the informants to be less effective, because it is still hampered by several factors such as differences in perception, slow response, and inadequate practice tools. However, interpersonal communication between lecturers and students becomes more flexible when done remotely using the help of the internet, because communication can be done minimally and at any time. It is hoped that interpersonal communication between lecturers and students remotely will be more interactive and varied in order to create an effective learning atmosphere.